Decision making in periodontal plastic surgery - Paolo Maturo; Edoardo Magnanelli; Raffaella Docimo (Annali di Stomatologia, 2025)
Preserving periodontal soft tissues (ST) is crucial to ensure long-term stability of dental health. Gingival recession (GR) can lead to both functional and aesthetic challenges, often necessitating surgical solutions. Techniques such as the coronally advanced flap (CAF), either alone or combined with grafts, have been documented as practical approaches. However, a significant drawback of autogenous grafts is the harvesting process, which extends the healing time at the donor site and increases patient discomfort. This study aims to evaluate the most reliable methods for addressing graft rejection (GR) using cellular allografts (CAF) along with a novel xenogeneic acellular dermal matrix (xeno-ADM), providing insight and guidance for clinicians in their decision-making process. A literature review was conducted from March to June 2020, using PubMed, the Cochrane Library, and manual searches of key journals, including the Journal of Periodontology, International Journal of Periodontics and Restorative Dentistry, Journal of Clinical Periodontology, and Journal of Periodontal Research. The investigation explored GR classification systems, surgical flap designs for root coverage procedures (RCP), and the graft types used in these interventions. All reviewed RCP techniques demonstrated reductions in recession depth (RD) and gains in clinical attachment level (CAL), making them viable for clinical use. Both CAF and tunnelling techniques are skill-intensive and require practice to achieve full root coverage. Xeno-ADM (NovoMatrix) emerges as a promising substitute for subepithelial connective tissue grafts (SCTG), offering ease of use, unlimited availability, reduced postoperative morbidity, rapid vascularization, and excellent tissue integration. However, additional research is warranted to assess its long-term stability at least one year after surgery.